Women and civil society in Turkey women's movements in a Muslim society - Çaha, Ömer 1964- (Routledge, 2016)
Focusing on three important interrelated issues, Women and Civil Society in Turkey challenges the classical definition, developed in the West, of civil society as an equivalent of the public sphere in which women are excluded. First it shows how feminist movements have developed a new definition of civil society to include women.